ATM inhibition enhances cancer immunotherapy by promoting mtDNA leakage and cGAS/STING activation - Mengjie Hu; Min Zhou; Xuhui Bao; Dong Pan; Meng Jiao; Xinjian Liu; Fang Li; Chuan‐Yuan Li (2020)
Novel approaches are needed to boost the efficacy of immune checkpoint blockade (ICB) therapy. Ataxia telangiectasia mutated (ATM) protein plays a central role in sensing DNA double-stranded breaks (DSBs) and coordinating their repair. Recent data indicated that ATM might be a promising target to enhance ICB therapy. However, the molecular mechanism involved has not been clearly elucidated. Here, we show that ATM inhibition could potentiate ICB therapy by promoting cytoplasmic leakage of mitochondrial DNA (mtDNA) and activation of the cGAS/STING pathway. We show that genetic depletion of ATM in murine cancer cells delayed tumor growth in syngeneic mouse hosts in a T cell–dependent manner. Furthermore, chemical inhibition of ATM potentiated anti–PD-1 therapy of mouse tumors. ATM inhibition potently activated the cGAS/STING pathway and enhanced lymphocyte infiltration into the tumor microenvironment by downregulating mitochondrial transcription factor A (TFAM), which led to mtDNA leakage into the cytoplasm. Moreover, our analysis of data from a large patient cohort indicated that ATM mutations, especially nonsense mutations, predicted for clinical benefits of ICB therapy. Our study therefore provides strong evidence that ATM may serve as both a therapeutic target and a biomarker to enable ICB therapy.